182k views
23 votes
Need answer fast with all the steps included please

Need answer fast with all the steps included please-example-1
User GrantByrne
by
4.7k points

1 Answer

7 votes

Answer:


((6x^2y)/(5))

Explanation:

Given


((2x)(3x^3y^2))/(5x^2y)

Required

Solve

Open the brackets


((2x)(3x^3y^2))/(5x^2y) =
((2x*3x^3y^2))/(5x^2y)


((2x)(3x^3y^2))/(5x^2y) =
((6x^4y^2))/(5x^2y)

Apply law of indices:


((2x)(3x^3y^2))/(5x^2y) =
((6x^(4-2)y^(2-1)))/(5)


((2x)(3x^3y^2))/(5x^2y) =
((6x^2y))/(5)


((2x)(3x^3y^2))/(5x^2y) =
((6x^2y)/(5))

User Marsman
by
4.4k points